Accounting - Warren, Carl S.; Jones, Jefferson P.; Tayler, William B. (Cengage, 2024)
"A major objective of Warren/Jones/Tayler Accounting, 29e, is to create an inclusive learning experience for all students that recognizes the wide diversity in student demographics, abilities, and experiences. This edition has been revised with a learner-centric approach that understands and acknowledges that a student's learning experience may be influenced by a variety of mental, sensory, and physical factors. As a result, this edition and its ancillaries have been designed to create an accessible learning experience for all students. This edition also recognizes that students have unique backgrounds and perspectives. As a result, chapter content, illustrations, and homework are designed to be respectful and inclusive of differences in student race, ethnicity, sexual orientation, gender, religion, age, and culture. The authors welcome suggestions and comments on how to be even more inclusive in future editions"--